Penerapan Pedoman Gizi Seimbang Pada Ibu Balita Di Kelurahan Babakan - Zohriatun Fitri; Abdul Salam (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. Basic Health Research in 2007 showed the prevalence Behave Properly In Hand Wash in Indonesia is 23.2%. NTB included into the 15 provinces below the national prevalence of only 14.2% of the population NTB that behaves properly in hand washing. In addition, the prevalence of physical activity to in Indonesia, namely 48.2%, and in the prevalence of physical inactivity NTB higher at 48.8%. Riskesdas data in 2013 showed that an increase in food consumption habits on society salty ≥10 years from 24.5% in 2007 increased to 26.2% in 2013. While the prevalence of data about fruit and vegetable consumption in the population aged 10 years up by 93.6% in 2007 and no significant change in 2013. To address the nutrition problems, need to be socialized balanced nutrition guidelines that can be used as guidelines for eating, physical activity, hygiene and maintain a normal weight. Research Methods. This study aims to determine the application of the guidelines in the Village Babakan balanced nutrition. This research was conducted with a descriptive observational research with a sample of 84 people. Data collected in the form of respondents age, education level of respondents and implementation of balanced nutrition guidelines in daily life. Research Result. Respondents who have aged <20 years 1 person, 20-35 years of age 63 and age> 35 years 20. Respondents who were taking education at most that 72.6% of Primary Education, Higher Education and at least 4.8%. The first pillar balanced nutrition applied by 44 of the respondents (52.4%), the second pillar of balanced nutrition applied by 50 of the respondents (59.5%) and no respondents are implementing the third and fourth pillars. 25% of respondents who apply pillars, namely 40 respondents, and applying 50% of respondents pillars 27 and 17 respondents did not apply pillars of balanced nutrition. Conclusion. The higher the educational level the application of the guidelines tend to be more well-balanced nutrition.